CDSS score is favorable to ISTH score on outcomes for disseminated intravascular coagulation in patients with liver transplantation: a retrospective cohort study - Li Zhong; Li Zhong; Yan Liu; Yan Liu; Conglin Wang; Lei Su; Lei Su; Zhifeng Liu; Zhifeng Liu; Zhifeng Liu; Ming Wu (Frontiers in Medicine)
BackgroundLimited data are available regarding disseminated intravascular coagulation (DIC) scores after liver transplantation (LT). As Chinese DIC Scoring System (CDSS) is widely accepted for assessing coagulation in China, this study was aimed to investigate the prognostic value of CDSS scores in patients with undergoing LT.MethodA retrospective cohort study was conducted on patients who underwent LT from November 2009 to October 2021. We validated CDSS criteria by comparing with International Society on Thrombosis and Hemostasis (ISTH) score. Additionally, its prognostic value was evaluated with receiver operating characteristic (ROC) curves and odds ratio based on mortality rates at 28, 60, and 90 days, as well as the correlations between the CDSS score and acute physiological and chronic health assessment II (APACHE II), sequential organ failure assessment (SOFA) scores at 90-day mortality.ResultsA total of 569 LT patients were enrolled, of which 80 patients developed DIC with CDSS score and 305 patients with ISTH score. Patients with DIC using the CDSS exhibited higher APACHE II and SOFA scores than those with ISTH score. The incidences of acute kidney injury, infection, lymphocytopenia and mortality were higher in DIC patients with CDSS than in those with ISTH. When assessing the prognostic value for 28-day mortality, the CDSS demonstrated higher sensitivity (64.61% vs. 50.77%), but lower specificity (73.62% vs. 88.89%) compared to the ISTH, the areas under ROC (AUC) for the CDSS and ISTH scores were 0.739, 0.741 (p < 0.05) and the odds ratios (OR) for the CDSS and the ISTH were 6.228, 3.597, respectively (p < 0.05). The ORs for predicting mortality with 60-day (7.719 vs. 3.95) and 90-day (7.582 vs. 3.95) criteria with CDSS were higher than those with ISTH (p < 0.05). The Spearman’s rank correlation coefficients between the CDSS and APACHE II scores, and the SOFA scores were 0.217 and 0.422, respectively, compared to 0.19 and 0.371 for the ISTH score (p < 0.001).ConclusionDisseminated intravascular coagulation presents a life-threatening complication in perioperative period of LT. The CDSS score has better prognostic value than the ISTH score for DIC patients after LT. A prospective randomized controlled study should be designed to further evaluate the findings.